(untitled) (Dristikon: A Multidisciplinary Journal, 2023)
The specific objective of this investigation was to explain the impact of personal remittance on the Gross Domestic Product of Nepal. This research used secondary data. Using data were received from different websites like websites of the World Bank, the Department of foreign employment, and so on. Collected data were analyzed and interpreted through Ms. Word, Ms. Excel, and IBM SPSS Statistics 26 version including statistical tools like descriptive and inferential. The study found that personal remittances received, and percent of female migrants had a moderate positive correlation but, a weak correlation coefficient with personal remittance received and the percentage of male migrants. Results cleared that there has no significant relationship between the no. of males and personal remittance received but there has a significant relationship between the no. of females and personal remittance received. As remittance income is increasing with the increase in the migrant population towards foreign. At the current time, Nepal is based on remittance income due to the lack of other sectors. Hence, the Nepalese government should pay attention to the proper utilization of remittance in productive sectors.